Developing Thai - English Bilingual Animation System to Promote Exercise Ability Among Elderly - Denduang, Prapon; Ruengwatthakee, Pimrawee; Pookhuntod, Wanchat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aims to 1. develop a bilingual (Thai and English) animation to promote exercise performance among older adults, and 2. examine the satisfaction of older adults with the bilingual animation. The study sample consisted of 94 older adults from Maidad Subdistrict, Bang Rachan District, Sing Buri Province, who were selected through purposive sampling among volunteers willing to participate in the research. The research tools included a bilingual animation (Thai-English) comprising 24 scenes and a 17-item satisfaction questionnaire. The data were analyzed using percentage, mean, and standard deviation. The results revealed that the developed animation features two older adult characters, one male and one female, demonstrating 12 different exercise movements in rhythm with music. Each exercise is accompanied by bilingual descriptions (Thai and English) displayed below the scenes. The results indicate that the overall satisfaction of older adults with the bilingual animation was rated at a very high level (Mean = 4.29, S.D. = 0.66).